The occurrence and associated risk factors of brain metastases in well differentiated grade 1 and 2 bronchial neuroendocrine tumours: A single centre retrospective analysis of 280 patients. (27th July 2022) - Spurgeon, Laura; Jones, James; Lewis, Alexandra; Rammohan, Kandadai; Shaheen, Fadhel; Weaver, Jamie; Papaxoinis, George; Mansoor, Wasat
Abstract: Typical and atypical bronchial carcinoid account for around 2% of all neuroendocrine neoplasms of pulmonary origin. Fewer than 5% of patients with these cancers are thought to develop brain metastases, and hence routine intracranial imaging is not currently included in staging investigations. In this study, retrospective case note analysis was performed on 280 patients diagnosed with either typical carcinoid (TC) or atypical carcinoid (AC) at a large, single‐site cancer centre. None of the 219 patients with TC developed brain metastases during the course of their disease, whereas seven of the 61 AC (11.5%) were found to have intracranial spread, four of which were present at the point of diagnosis. A Cox proportional hazard model showed that a Ki‐67 expression ≥18%, patient age ≥65 years and disease stage at diagnosis were all independently and significantly associated with the development of brain metastases in AC. This study has found new evidence that the incidence of brain metastases in AC is significantly higher than previously thought. Of all the variables reviewed, Ki‐67 expression was most strongly associated with the development of intracranial disease in AC and could be readily translated into clinical practice. Predictive factors such as age, disease stage and Ki‐67 expression could be used to identify patients at particularly increased risk of brain metastases, who would benefit from early intracranial imaging. This could allow for earlier detection and treatment of metastases, with the potential to improve clinical outcomes and patient quality of life. Abstract : >10% incidence of brain metastases in atypical bronchial carcinoid with Ki67 expression strongest associated risk factor.